Pengaruh Model Pembelajaran Kooperatif Tipe Gallery Walk terhadap Minat dan Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas VIII di SMP Negeri 1 Bandung Tulungagung - Nurul Ulfatun Anjelina; Dita Hendriani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This research is motivated by the lack of optimal students' understanding of social studies materials. Students tend to think that social studies materials focus more on recall and memorization. As a result, interest in learning is low, will have an impact on unsatisfactory learning outcomes. A learning model is needed to increase student involvement, so that interest and learning outcomes increase, one of which is gallery walk-type cooperative learning. The formulation of the problem in this study is (1) Is there an effect of the gallery walk type cooperative learning model on students' learning interest in social studies class VIII at SMPN 1 Bandung Tulungagung? (2) Is there an effect of the gallery walk type cooperative learning model on student learning outcomes in social studies class VIII at SMPN 1 Bandung Tulungagung? (3) Is there an effect of the gallery walk type cooperative learning model on students' interest and learning outcomes in social studies class VIII at SMPN 1 Bandung Tulungagung?. There are several objectives taken from the background of these problems in general, namely it is expected to determine the influence of the gallery walk-type cooperative learning model on students' interests and learning outcomes in social studies subjects in grade VIII at SMPN 1 Bandung. The approach of this research uses a quantitative method with a quasi experimental type, a nonequivalent control group design. The sample consisted of students in class VIII F as the control class and VIII J as the experimental class, each totaling 32 students. The sampling technique used is purposive sampling. Data is collected through questionnaires, tests, and documentation. The data analysis included instrument tests, prerequisite tests, and hypothesis tests. The results of this study are (1) There is an effect of the gallery walk type cooperative learning model on the learning interest of grade VIII students in social studies subjects at SMPN 1 Bandung Tulungagung. Independent test sample t-test sig.(2-tailed) 0.000 < 0.05 then H0 rejected H1 accepted. (2) There is an influence of the gallery walk type cooperative learning model on student learning outcomes in social studies subjects at SMPN 1 Bandung Tulungagung. Independent test sample t-test sig.(2-tailed) 0.000 < 0.05 then H0 rejected H1 accepted. (3) There is an influence of the gallery walk learning model on students' interests and learning outcomes in social studies subjects at SMPN1 Bandung Tulungagung. A change in the value of the sig. (2-tailed) 0.000 < 0.05 then H0 rejected H1 accepted.